Allodynia is more frequent in the individuals with more intense attacks of headache and in women - Silva, Gêssyca Adryene de Menezes; Bringel, Simone de Siqueira; Martins, Hugo André de Lima; Ximenes, Rosana Christine Cavalcanti; Valença, Marcelo Moraes; Oliveira, Daniella Araújo de (Headache Medicine, 2012)
Objective: Identifying the presence of allodynia in students with primary headache in a college. Method: It was evaluated 378 students (273 women) aged between 18 and 45 years (22 ± 5 years). A questionnaire was used on the clinical characteristics of headache based on ICHD II-2004 criteria, and another one for the identification and differentiation of cephalic and extra-cephalic allodynia. Results: In this sample 374/378 (98.9%) students had headaches throughout life [271/273 (99.3%) females and 103/105 (98.1%) men, p= 0.309; χ2] and 334/378 (88.4%) complained of headache in the last three months [248/273 (90.8%) women and 86/105 (81.9%) men, p=0.020; χ2]. Of the students with headache in the last three months 331/378 (87.6%) had allodynia [250/273 (91.6%) women and 81/105 (77.1%) men, p<0.001; χ2]. There was an association between the intensity of the headache in the last three months and the presence of allodynia [5/12 (41.7%) of the individuals with mild pain, 211/236 (89.4%) moderate pain and 83/86 (96.5%) severe pain; p<0.001; χ2]. Cephalic allodynia was more frequent in conditions such as combing the hair (43.5) the use of ponytail (57.3%), use of glasses (33.7%), use of hat or cap (53.6% women and 59.3% man), exposure to coldness (45.6% women and 41.9% man) and heat exposure (56.9% woman and 50% men). The extracephalic allodynia was more frequently triggered in heat exposure (60.9% women and 59.3% men) and coldness (42.7% women and 38.4% men). Conclusion: Allodynia is more frequent in women and in individuals with more intense attacks of headache.